2015
DOI: 10.1089/dna.2014.2688
|View full text |Cite
|
Sign up to set email alerts
|

RUNX2: A Master Bone Growth Regulator That May Be Involved in the DNA Damage Response

Abstract: RUNX2 is a member of the RUNX family of transcription factors, also containing the RUNX1 and RUNX3 proteins. These factors control the expression of genes essential for proper development in many cell lineages. RUNX2 plays a crucial role in the proliferation and differentiation of osteoblasts, required for bone formation. The cellular level of RUNX2 oscillates in a cell phase-specific manner, reaching a maximum at G2/M in some cells and overexpression of RUNX2 in osteoblasts blocked G1 to S phase progression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 109 publications
1
32
0
Order By: Relevance
“…Runt-related transcription factors 2 (Runx2) is a key specific regulator of osteoblast differentiation, and its mutation associates with human cleidocranial dysplasia [7][8][9]. Runx2 stimulates the maturation of osteoblasts during bone differentiation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Runt-related transcription factors 2 (Runx2) is a key specific regulator of osteoblast differentiation, and its mutation associates with human cleidocranial dysplasia [7][8][9]. Runx2 stimulates the maturation of osteoblasts during bone differentiation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Runt-related transcription factor 2 (Runx2), is identified as a "master gene" required for osteoblastic differentiation process from mesenchymal precursors (Tu et al, 2007b;Vimalraj et al, 2015;Wysokinski et al, 2015). Our previous studies, showed that, haploinsufficiency of Runx2 results in decreased bone formation and changes in BSP expression patterns (Li et al, 2005a;Tu et al, 2007bTu et al, , 2008Tu et al, , 2009).…”
mentioning
confidence: 99%
“…Cells in the G2 and M phases of the cell cycle are sensitive to interventions such as 5-FU and radiation [30, 32]. To determine the cell cycle progression of colorectal cancer cells after treatment with 5-FU, exponentially growing cancer cells were exposed to 5-FU and then were analyzed by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%